Kraft Pulping of Elaeodendron Glaucum - Karira, B. G.; Dhawan, Rita (Indian Forester, 1985)
Unbleached pulp in 47-52% yield suitable for wrapping paper could be produced from Elaeodendron glaucum by kraft (sulfate) process using 14-20% active alkali. The pulp having kappa number 25 was bleached by CEH sequence to give a pulp yield of 44% having 72% (Elrepho) brightness and satisfactory strength properties for the production of writing and printing papers.